Asosiasi Gaya Belajar De Porter & Hernacki dengan Hasil Belajar Matematika Siswa SMP (Universitas Muhammadiyah Purworejo, 2023)
Student learning styles can influence their learning outcomes. Sometimes, a student's learning style in class can pose an obstacle for other students, as it may hinder their ability to focus on receiving lessons. The aim of this research is to investigate the relationship between learning styles and mathematics learning outcomes. The method is quantitative research utilizing correlation techniques. Random sampling was conducted among class VIII students of SMP Negeri 4 Cikarang Selatan. The research instrument for measuring learning styles was a questionnaire, while mathematics learning outcomes were assessed using multiple-choice tests. Pre-requisites for analysis included normality testing (Lilliefors test) and simple linear regression test (ANOVA). The results indicated that both variables were normally distributed, and the regression test demonstrated that mathematics learning outcomes were influenced by linear learning styles. Based on Pearson's product-moment correlation test calculations, it can be concluded that there is a significant positive relationship between learning styles and mathematics learning outcomes for students at SMP Negeri 4 Cikarang Selatan.